Non-recurrent Laryngeal Nerve During Intraoperative Neuromonitoring Thyroidectomy: A Case Report and Literature Review - Davide Inversini MD; Simone Gianazza MD; Matteo Annoni MD; Andrea Leotta MD; Dorotea Confalonieri MD; Enrico Ferri MD; Andrea Palillo MD; Andrea Vigezzi MD; Sabrina Garbarino MD; Giuseppe Ietto MD; Giulio Carcano Prof Dr (SAGE Publishing, 2024)
Complete and precise knowledge of the neck anatomy and its eventual anomalies is crucial while performing a safe thyroid and parathyroid surgery. Embryo-genetic malformations of the IV branchial arch can lead to an uncommon anatomical alteration known as non-recurrent inferior laryngeal nerve. Its prevalence varies between 0.7% for the dextral branch and 0.04% for the sinistral. In these cases, the inferior laryngeal nerve branches originate directly from the cervical vagus nerve, entering the larynx without hooking, on the right side around the subclavian artery or on the left around the aortic arch. The presence of a non-recurrent laryngeal nerve is challenging, due to the increased risks of iatrogenic damage to the nerve, which results in hoarseness, dysphagia, glottal obstruction, vocal cords palsy, and serious airway impairment. We present the case of a 58-year-old woman. The patient was admitted to our department for a nodule classified as Bethesda IV in the right thyroid lobe. Through the use of intraoperative neuromonitoring (IONM), surgeons detected intraoperatively a non-recurrent laryngeal nerve. A subsequent computed tomography scan confirmed an anomalous right subclavian artery branching from the left aortic arch, the Lusoria Artery. Anatomical variants represent pitfalls in this case and an accurate knowledge of the neck region is imperative while performing thyroid surgery. Devices such as IONM are useful for detecting abnormalities that may lead to iatrogenic damages.